2003
DOI: 10.1101/gr.1276503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel ErbB3-Interacting Factors Using the Split-Ubiquitin Membrane Yeast Two-Hybrid System

Abstract: Analysis of membrane protein interactions is difficult because of the hydrophobic nature of these proteins, which often renders conventional biochemical and genetic assays fruitless. This is a substantial problem because proteins that are integral or associated with membranes represent approximately one-third of all proteins in a typical eukaryotic cell. We have shown previously that the modified split-ubiquitin system can be used as a genetic assay for the in vivo detection of interactions between the two cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 42 publications
0
63
0
2
Order By: Relevance
“…Interestingly, several transcription factors have been found to associate with ErbB-3 in yeast two-hybrid approaches, including p23/p198 protein (also known as Ebp1; ref. 33), early growth response-1 (34), and the zinc finger protein ZNF207 (34). Yoo, Zhang, and others showed that treating AU565 breast cancer cells with the ErbB-3 ligand heregulin resulted in dissociation of Ebp1 from ErbB-3 and subsequent translocation of Ebp1 to the nucleus, where it suppressed androgen receptor-mediated gene transcription (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several transcription factors have been found to associate with ErbB-3 in yeast two-hybrid approaches, including p23/p198 protein (also known as Ebp1; ref. 33), early growth response-1 (34), and the zinc finger protein ZNF207 (34). Yoo, Zhang, and others showed that treating AU565 breast cancer cells with the ErbB-3 ligand heregulin resulted in dissociation of Ebp1 from ErbB-3 and subsequent translocation of Ebp1 to the nucleus, where it suppressed androgen receptor-mediated gene transcription (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…PCR products of the ERG28 bait and the 14 preys (14 ergosterol biosynthetic enzyme open reading frames) were digested and cloned into the bait (pCub) and prey (pNub) vectors, respectively (14). The bait construct (pERG28-Cub-TF) and all of the prey constructs (pERGX-HA-Nub) were transformed into the L40 yeast reporter strain and grown on CSM-Leu and CSM-Trp, respectively.…”
Section: Cloning Of the Prey Pergx-ha-nub Constructsmentioning
confidence: 99%
“…The bait vector, pCYC-BAIT-Cub-TF (pCub), and prey vector, pADH-PREY-HA-Nub (pNub), were kindly provided by Dr. Igor Stagljar (14). pCub is a CEN plasmid containing LEU2 and a weak yeast CYC1 promoter, multiple cloning sites followed by the C-terminal Cub sequence, and a TF consisting of protein A, LexA, and VP16.…”
Section: Primer Design and Pcr Cloningmentioning
confidence: 99%
See 2 more Smart Citations